The Effectiveness of Loving Massage on Sleep Quality in Third Trimester Pregnant Women at Pmb Deliana, Marpoyan Damai District, Pekanbaru City in 2020 - Intan Widya Sari; Rina Yulviana (Journal of Midwifery and Nursing, 2021)
Pregnancy is a period of crisis in a woman's life process. The period in which changes occur in all body systems, including the cardiovascular, respiratory, hormonal, gastrointestinal, and musculoskletal systems. Pregnant women during pregnancy experience physical and psychological changes that can cause discomfort from the 1st to 3rd trimesters.One of them is the enlargement of the uterus, it will affect the fulfillment of sleep rest because of difficulty in determining a comfortable position, besides hormonal changes can cause psychological changes in pregnant women making it difficult to meet and maintain sleep. Sleep is an important factor in overall health. Improving sleep quality can be done in many ways, which among them are pharmacological and non-pharmacological techniques. Pharmacological method is a therapy commonly given to sleep disorder sufferers which functions to reduce anxiety, stress and give calm. But not for pregnant women, because it has the potential to increase the risk to the fetus and its impact on fetal growth and development. Therefore, choosing to use a non-pharmacological method is more appropriate, because its use has less side effects compared to pharmacological methods. One of the non-pharmacological techniques that can be given to overcome sleep difficulties in pregnant women includes relaxation techniques such as loving massage, yoga, progressive muscle relaxation, massage, music therapy, meditation, swimming, deep breathing techniques and walking.